The Complex Role of the Microbiome in Non-Small Cell Lung Cancer Development and Progression - Souza, Vanessa G. P. [UNESP]; Forder, Aisling; Pewarchuk, Michelle E.; Telkar, Nikita; de Araujo, Rachel Paes [UNESP]; Stewart, Greg L.; Vieira, Juliana; Reis, Patricia P. [UNESP]; Lam, Wan L. (MDPI, 2023)
In recent years, there has been a growing interest in the relationship between microorganisms in the surrounding environment and cancer cells. While the tumor microenvironment predominantly comprises cancer cells, stromal cells, and immune cells, emerging research highlights the significant contributions of microbial cells to tumor development and progression. Although the impact of the gut microbiome on treatment response in lung cancer is well established, recent investigations indicate complex roles of lung microbiota in lung cancer. This article focuses on recent findings on the human lung microbiome and its impacts in cancer development and progression. We delve into the characteristics of the lung microbiome and its influence on lung cancer development. Additionally, we explore the characteristics of the intratumoral microbiome, the metabolic interactions between lung tumor cells, and how microorganism-produced metabolites can contribute to cancer progression. Furthermore, we provide a comprehensive review of the current literature on the lung microbiome and its implications for the metastatic potential of tumor cells. Additionally, this review discusses the potential for therapeutic modulation of the microbiome to establish lung cancer prevention strategies and optimize lung cancer treatment.
Keywords: immunotherapy; lung cancer; microbiome; tumor microenvironment (TME)